Unexplained Air Disasters: Compensation for Indirect Victims - Jean Michel Haziza (Advanced Space Law)
The air disaster of Malaysia Airlines Flight MH370, which disappeared on March 8, 2014, remains an enigma. The reasons for the deaths of the passengers and crew remain unexplained even after ten years of fruitless searches. Although the Malaysian government may relaunch the search for the missing plane this year, nothing can erase the moral trauma suffered by the indirect victims. The moral and financial repercussions on the indirect victims of passengers who died in an unexplained air disaster manifest as a feeling of not being able to grieve due to the lack of obvious causes of the accident. While international legal texts provide frameworks for compensating the damage suffered, national courts apply compensation scales that are inequitable among indirect victims. To address current inequities, recognizing the prejudice of waiting and worry could alleviate the suffering endured by indirect victims.